Strategy Analysis to Improve Competitiveness of PT Van Oord Indonesia Jakarta - M. Fachrurrozi; Besar Agung Martono (www.amertainstitute.com, 2024)
This study aims to analyze the strategic position of PT Van Oord Indonesia in facing challenges and opportunities in the maritime dredging and reclamation industry. The focus of the research is to identify internal strengths and weaknesses, as well as external opportunities and threats that affect the company's competitiveness. This study uses a descriptive approach with qualitative methods through interviews, observations, and document analysis. The IFE, EFE, CPM, IE, SWOT, and QSPM matrices are used to identify strategic positions and determine strategic priorities. The results show that PT Van Oord Indonesia is in Quadrant I of the IE (Growth Strategy) Matrix with a total IFE score of 3.18 and EFE of 3.50. The proposed strategy includes diversification of services based on green technology and development of local workforce. The implementation of this strategy is expected to increase competitiveness and support the company's business sustainability.